The Effect of Economic Growth on Multidimensional Poverty - Tri Wandita, Desliyani; Gunarto, Toto; Ratih, Arivina (Journal Research of Social Science, Economics, and Management, 2022)
Poverty is a complex problem, so a more appropriate approach is needed to represent this complex phenomenon and multidimensional reality. This study aims to analyze the effect of GRDP per Capita on multidimensional poverty. The method used to measure multidimensional poverty in this study is the Alkire Foster method. The multidimensional poverty index that was built refers to the index developed by Alkire and Santos, as well as several previous studies with several changes that were adjusted to the availability of data. The results of this study resulted in panel data regression analysis and involved the HDI control variable. It was found that partially, economic growth as measured by gross regional domestic product per capita at constant market prices in 2010 had no significant effect on the multidimensional poverty rate in Lampung Province, Indonesia 2017-2019.